Essential Points to Achieve Effective Inhaler Technique Training for Asthma and COPD Patients - Hiroyuki Ohbayashi (Disease and Health Research: New Insights Vol. 5, 2024)
The recent increase in the range of inhaled medications has expanded treatment options but also complicated treatments due to the diverse inhalation devices. Patients with asthma and chronic obstructive pulmonary disease (COPD) must take the agent at the indicated dosage and use the inhaler device correctly. However, it is often difficult to achieve sufficient performance. Inhalation therapy involves two types of adherences: to the drug and to the procedures for the inhalation device. It is crucial to view inhalation guidance as a means to enhance and maintain patient adherence to inhalation therapy. This review presents eight essential points for training patients with asthma and COPD in effective inhaler techniques. These points help ensure a balance of adherence to both the medication and the inhalation device, thereby maintaining disease control in clinical settings. It is concluded that favorable patient adherence and disease control can be achieved by providing ongoing inhaler technique training in clinical settings.